The protection of digital rights: A European identity issue - Lazari, Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The storage of personal data does not endanger only the so-called individual right to privacy, but covers a wider social and political spectrum, related to the health of democratic life. Faced with the Chinese sovereignty vision and the segmented and mercantilist American idea of digital security, the European Union has been proposing in the last decade a conception closely linked to the jurisprudence of the CJEU around the essence of the fundamental right to digital identity. The primary issues that arise when studying cybersecurity must be addressed from a broader, (arguably, inevitably existential) perspective, underlining that cybersecurity refers to public goods and private property and that the organizations and bodies designated to protect them must be subject to the scrutiny of constitutionally relevant norms, lest they become true CyberLeviathans. This study addresses the essential aspects of data protection and citizens’ rights in the new globalization era, designing a strategic framework where both within the territory of the Union and outside it the Community institutions must necessarily dialogue on the scope of fundamental rights in the face of the requirements of national security.
Keywords: Digital Rights; European Union Law; Court of Justice of European Union; European Union Identity